LATIHAN MIRROR THERAPY SEBAGAI UMPAN BALIK VISUAL PADA ESKSTREMITAS DENGAN HEMIPARESIS PASIEN PASCA STROKE KETIKA PERAWATAN MANDIRI DIRUMAH - Ni Putu Diah Ayu Rusmeni; Nurul Imam; Khalifatus Zuhriyah Alfianti (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2025)
Introduction: Post-stroke patients often have difficulty carrying out normal activities, even if they can only sit in a wheelchair. It was recorded that 28.5% of stroke sufferers died and the rest suffered partial or even total paralysis. There is a need for management that can overcome the problem of hemiparesis in post-stroke patients. Efforts that can be made are mirror therapy exercises, this is an exercise that is relatively simple, cheap and can be done at home. Objective: This study aims to determine the effectiveness of mirror therapy in post-stroke patients with hemiparesis who are undergoing independent treatment at home based on a study from the last 9 years. Method: The research design used the Preferred Reporting Items for Systemic Review and Meta-Analysis (PRISMA) Guidelines with an online literature search strategy using the Google Chrome search engine Scopus, Science Direct, PubMed and Proquest. The literature source years taken were from 2014 to 2022. Results: Research from 8 journals reviewed showed that mirror therapy was effective in treating hemiparesis in post-stroke patients. Mirror therapy exercises for 4 weeks with a dose of 1 time a day in the morning, with a duration of 5-7 minutes. Conclusion: Mirror therapy is a therapy that can be used to treat hemiparesis problems in post-stroke patients, which is simple, cheap and can be done at home.